PHYSICHOCEMICAL COMPOSITION OF COLLAGEN SEA CUCUMBER (Paracaudina australis) IN EXTRACT WITH ACID DIFFERENT CONCENTRATION OF ACETATE - Wahyu Tawisna; Andarini Andarini; Edison Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTBerunok is a type of marine biota that lives on muddy coasts and seagrasses but has not high economic value. This study aimed to determine the effect of different concentrations of acetic acid on the yield and chemical composition of collagen from sea cucumbers. The research method used was a non-factorial completely randomized design (CRD) with 3 treatment levels by repeating 3 times, namely 0.50 M acetic acid concentration, 0.75 M acetic acid concentration and 1 M acetic acid concentration. Parameters for analysis were analysis yield, and chemistry (water and protein). The results showed that the yield values extracted with acetic acid concentrations of 0.50 M, 0.75 M and 1 M were 2.74%, 3.56% and 5.07%, respectively. The chemical composition consisted of water content and protein extracted with acetic acid concentrations of 0.50 M, 0.75 M, 1 M respectively 17.15%, 14.21%, 11.54% and protein successively 75.69 %, 78.26%, and 79.21%. Keywords: Collagen, yield, Proximate Sea Cucumber